Selected Aspects of Frost Protection Using Extruded Polystyrene for the Designed Road Surface - Partyka, Jacek; Wysoczański, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The present article delves into the consequences of subzero temperatures on the integrity of road elements, specifically scrutinizing their load-bearing capabilities and structural resilience. Central to the discourse is the elucidation of frost heave mechanisms, alongside an exposition of the overarching principles underpinning frost protection strategies within the framework of Polish engineering protocols. Attention is directed towards the deployment of extruded polystyrene as a pivotal component in fortifying road structures against frost-induced degradation. Moreover, the article encompass the preliminary conjectures on the adoption of insulating materials, prevalent in Anglo-Saxon jurisdictions, which offer promising prospects for enhancing frost protection measures in Polish road design, particularly within the context of bespoke structural configurations.
Keywords: frost protection; extruded polystyrene; frost index